Biopolitik Perempuan Muslim, Feminisme dan Demokrasi: Studi Di Banda Aceh dan Padang - Inda Kartika (Jurnal Identitas, 2023)
Feminism exerts influence in the social and political life of women even for men and children, young people and the elderly. Hence, exploring feminism has experienced a lot of criticism among academics, the public, policymakers, and even the state. Thus, this study explores feminism and biopolitics, whereas a theory of feminism is not only a spirit but merged in the women’s struggle movement. Additionally, this study investigates of how Muslim women use politics to fulfil their interests; What society would be like if men and women were in different conditions in terms of health, treatment, care, birth and death; and how the principles of feminism are used to address women’s biopolitical problems. This research uses biopolitics as an analysis to see women in Muslim-majority areas involved in democratic public spaces and open Islamic views to inclusive women. This study collected data from interviews and ethnographic methods. The setting is the local areas of Banda Aceh and Padang. This study reveals that there is state injustice based on biopolitical fulfilment which is an obstacle for Muslim women to fight for various interests, such as women’s bodily rights related to pregnancy regulation, political rights in parliament, providing adequate access to health for victims of birth sexual violence, state social control, religion and local culture making women unable to achieve fulfilment of rights, especially women’s access to fulfilment of rights and authorities Biological. Furthermore, this article also discusses the principles of feminism used to overcome women’s biopolitical problems.